2002
DOI: 10.1590/s0100-204x2002000600005
|View full text |Cite
|
Sign up to set email alerts
|

Equações para a estimativa do índice de área foliar do cafeeiro

Abstract: Resumo -Com o objetivo de estudar a variação temporal do índice de área foliar (IAF) da cultura de café, utilizando um método simples e não-destrutivo, foi instalado um experimento no Departamento de Produção Vegetal, da Escola Superior de Agricultura Luiz de Queiroz, da Universidade de São Paulo. Utilizou-se a cultivar Mundo Novo IAC 388-17, enxertada sobre a cultivar Apoatã IAC 2258 (de 15 até 35 meses de idade), no espaçamento de 2,5 x 1,0 m. Foram coletadas todas as folhas de duas plantas de café, em inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
51

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 1 publication
3
45
0
51
Order By: Relevance
“…oleifera) is a cold-season oilseed plant cultivated in Southern Brazil (Krüger, 2011). Its yield is influenced by different environmental, physiological and morphological factors, among which leaf area (LA) is a parameter indicative of crop yield, since biomass accumulation occurs through photosynthesis and the leaf is the main plant organ, responsible for gas exchanges and light energy interception (Pereira et al, 1997;Favarin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…oleifera) is a cold-season oilseed plant cultivated in Southern Brazil (Krüger, 2011). Its yield is influenced by different environmental, physiological and morphological factors, among which leaf area (LA) is a parameter indicative of crop yield, since biomass accumulation occurs through photosynthesis and the leaf is the main plant organ, responsible for gas exchanges and light energy interception (Pereira et al, 1997;Favarin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A quantifi cação da área foliar de uma cultura é importante em estudos de crescimento, uma vez que a fotossíntese realizada depende da interceptação da energia luminosa pelo dossel e da sua conversão em energia química (FAVARIN et al, 2002). Para a quantifi cação da área foliar, existem métodos diretos e indiretos de estimação da área foliar.…”
Section: Introductionunclassified
“…Barbosa et al (2012), when estimating LAI, found that the variability of the shape of crowns and the geometry of leafless regions were the properties that most strongly explained coffee's LAI. Also working with coffee, Favarin et al (2002) …”
Section: Resultsmentioning
confidence: 99%
“…The productive performance of a crop can be assessed throughout its growth by monitoring the plant leaf area (Sanpedro et al 2008), as the photosynthetic process depends on the interception of photosynthetically active radiation and its conversion capacity into chemical energy (Favarin et al 2002, Godoy et al 2007). …”
Section: Introductionmentioning
confidence: 99%